TANGGAP PERTUMBUHAN TANAMAN GANDUM TERHADAP NAUNGAN - Gagad Restu Pratiwi (Widyariset, 2010)
The aim of this research was to study the effects of shading intensity on growth of wheat. The research was designed with two factorials as a split plot. The first factor was the shading intensity and the second factor was thetime of shading. In addition, there was one treatment of without shading. The obtained data were analyzed by using the variance analysis and for the significant analysis treatment was contrast orthogonal and Duncan’s MultipleRange Test at the level significant 5%. The results showed that the shading treatment caused changes in micro environment around the crop. The 50% shading increased the vegetative phase of crop. In addition, the increasingintensity of shading also decreased rate transpiration, the number of fertile tiller per hill, and the number of spikes per square meter.